DESIGNING ENGLISH LANGUAGE PROGRAM AT PESANTREN: A NEED ANALYSIS OF COURSE DESIGN - Hanna Sundari; Lutfiansyah Lutfiansyah (Faktor Jurnal Ilmiah Kependidikan, 2021)
Pesantren is an Islamic educational institution with a boarding school system. Mostly in modern pesantren, the students learn and use Arabic and English among the use of local and national languages. Designing English course in specific context such as pesantren should consider systematic procedures. This current study was the initial step in course design, called need analysis, to collect information about the learners’ need. The framework of course development by Graves was applied, and the instruments were questionnaire and interviews. Moreover, pesantren stakeholders including teachers, students, and head of language center were recruited to be participants on the research. The findings show dimensions of present situation and future expectation on English course. It covers the purpose and objectives in learning English. The students’ goal in learning English is to communicate with people in nearest community and to continue study. The preferences in teaching method and recommended topics are also searched from both students and teachers. Making dialogues and conversation becomes the most preferable method completed with topics related to family life, school life, education, science and technology. Both teachers and students agree that the policy of full English system is important and necessary.